ENVIRONMENTAL HAZARDS AND LABOUR PROTECTION IN AGRICULTURE WITH THE ORGANIC FARMING DEVELOPMENT: A MODEL OF INTEGRATED ASSESSMENT - N. N. Novikov; N. T. Sorokin; N. N. Grachev; I. S. Mashkov; M. E. Denisova; V. S. Nikitin; M. M. Varfolomeeva; V. F. Evtyukhin (Юг России: экология, развитие, 2019)
The aim of the research is the assessment of environmental hazards and occupational safety to implement the most effective ways to protect workers, the environment from the effects of hazardous and harmful factors when using chemicals in agriculture.Research methods: monographic, abstract‐logical, mathematical and logical‐linguistic modeling, computational‐ constructive, probability theory, expert estimates, etc.Results: a model of integrated assessment of environmental hazards and labor protection in agriculture, including nine assessment blocks: 1) soil contamination by pesticides, agrochemicals and heavy metals; 2) the balance of nitrogen, phosphorus and potassium, ensuring environmental protection; 3) the load of livestock on pastures; 4) the ratio of stabilizing and destabilizing factors; 5) the risk of waste and by‐products; 6) the production of environmentally safe products; 7) working conditions in the workplace; 8) the level of investment in labor protection, environment and environmentally safe products; 9) the level of environmental culture and culture of labor protection of workers and the population.Conclusion: the Model is tested in the working conditions of LLC  ʺMalinischiʺ of the Pronsky district of the Ryazan region in manual mode and can be the basis for the implementation of information and computer technology assessment.